Build your own Raspberry PI project - Raeesha Bhanu Sheik Alaudeen (Nanyang Technological University, 2020)
‘Build your own Raspberry PI project,’ is an implementation of Internet of Thing (IoT) into industrial application. IoT is able to remotely control or monitor a system through internet network without physical interaction. The project focuses on building a coupled tank control system via a local network. The tank that is used in this project is Kentridge coupled tank system. Kentridge coupled tank system is a coupled multivariable tank system with 2 inputs and 2 outputs. It consists of two tanks side by side separated by a divider plate in-between. The small opening at the base of the two tanks let the water interact, flowing on either direction. Due to its non-linear nature, PID controller is used to efficiently achieve the objective (setpoint). The coupled tank control system was built with a python programming language to control the sensors and actuators in the tank with PID. Graphical User Interface (GUI) is built for the user to monitor and control the system. The front-end GUI was built using programming languages that comprise of Hypertext Mark-up Language 5 (HTML5) and Cascading Style Sheets (CSS). The back-end comprises of JavaScript and python programming for the coupled tank control system incorporating PID control. In addition, for the system to be monitored and controlled remotely via a webpage (HTTP), Flask micro framework platform is used to set Raspberry PI as a local webserver.